The Local Wisdom Value Of Mandhasiya Tradition (Study of Hindu Education) - Heny Perbowosari (Institut Hindu Dharma Negeri Denpasar, 2019)
Mandhasiya tradition is one of the local wisdom that is still carried out by the Gumeng Village community in Jenawi District, Karanganyar Regency. This tradition is believed by the community as a sacred and religious meaning, so the community is still encouraged to carry out this ritual. This study aimed at describing the reasons of Gumeng villagers to keep maintaining the Mandhasiya tradition, especially the local wisdom value of the Mandhasiya Tradition in the study of Hinduism education in Gumeng Village, Jenawi District, Karanganyar Regency and the implications of the Mandhasiya tradition toward Hindu communities in Gumeng Village, Jenawi District, Karanganyar Regency.This study used a qualitative method with a socio-cultural phenomenology approach. The primary data were collected by direct observation and interviews, while the secondary data by the exploration of journals, research results, and relevant literature sources. The results of this study concluded that 1) The reason to keep maintaining the Mandhasiya tradition by the Gumeng village community in Jenawi Subdistrict, Karanganyar Regency because of the desire to preserve the Javanese culture, ask for salvation to the Almighty God, maintain harmony among people, as well as trust in myths 2) Mandhasiya tradition have values of local wisdom based on the study of Hindu religious education, they are: religious values (Sraddha), togetherness values (Tat Twam Asi), environmental preservation values (Tri Hita Karana), sincerity values (Yajna), 3) implications of the Mandhasiya Tradition toward the society in Gumeng village, Jenawi Subdistrict, Karanganyar Regency is strengthening the community religiosity, strengthening solidarity, being involved in collective worship, and creating community welfare.